Efecto de granulometrías de calcio en morfometría de órganos digestivos y parámetros productivos en pollos de engorde - Nevárez Pacheco, Javier Andrés (2024)
This study evaluated the impact of the addition of granulated calcium in feed on the morphometry of digestive organs and productive parameters in broiler chickens. 200 COBB500 chickens were used, distributed in five treatments: a control without addition (T0) and four treatments with calcium of different sizes (3 mm, 4 mm, 5 mm and 6 mm) at 1%. Variables such as weight, weight gain, feed consumption, feed conversion, carcass yield and characteristics of the digestive organs were measured at 21 and 42 days. The results indicated that there were no significant differences in the productive parameters (p>0.05), although a trend towards reduction in feed consumption and an improvement in feed conversion was observed with the addition of calcium. However, significant differences were found in the diameter of the liver (P-value <0.00) and the gizzard with (P-value <0.04) at 21 days in favor of T1 and T0 respectively, as well as in the liver length with (P-value <0.02) at 42 days in which T0 obtained the highest value followed by T1. Despite the morphometric findings, the cost-benefit ratio showed a deficit in all treatments, with losses of 0.04 to 0.19 cents per dollar invested. It is concluded that calcium granulometry did not have a significant effect on production parameters and morphometry, possibly influenced by factors such as barn conditions, climate, feed quality and the high cost of feeding.